THE SYNTACTICAL LEVEL IN STYLISTIC ANALYSIS: UNRAVELING THE ART OF SENTENCE STRUCTURE AND VARIETY - Ro’zabonu Abduqayumova Shavkat qizi; Zilola Abdurakhmanova Yoqubjon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Abstract: The study of stylistics has long delved into the intricate tapestry of literary expression, wielding the tools of language to unravel the artistry and nuances embedded in texts. At the syntactical level, the analysis of sentence length, structure, types, and variety emerges as a critical dimension in deciphering the stylistic flourishes deployed by authors. This article endeavors to explore the multifaceted role of sentence length, structure, types, and variety in conducting stylistic analysis, drawing from seminal works and theoretical frameworks. By unraveling the interplay of syntactic elements within literary texts, this article aims to shed light on the profound impact of syntax on literary style and the potential insights it offers into the art of textual composition.